2006
DOI: 10.1677/joe.1.06970
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid, a histone deacetylase inhibitor, enhances sensitivity to doxorubicin in anaplastic thyroid cancer cells

Abstract: Multimodality treatments (i.e. surgery, chemotherapy, and radiotherapy) are recommended for anaplastic thyroid carcinoma (ATC), an extremely lethal human cancer, but to date there is little evidence that such approaches improve survival rates. It is thus necessary to seek new therapeutic tools. Histone deacetylase (HDAC) inhibitors are a promising class of antineoplastic agents that induce differentiation and apoptosis. Moreover, they may enhance the cytotoxicity of drugs targeting DNA through acetylation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 42 publications
3
79
0
1
Order By: Relevance
“…preclinical and clinical data indicate that HDACi may interfere with the expression of pro-and anti-angiogenic genes, suggesting a synergistic effect when HDACi are combined with anti-angiogenic agents such as the anti-VEGF antibody, bevacizumab (28). In addition, HDACi have been observed to potentiate the cytotoxicity of anthracycline-type topoisomerase (topo) II inhibitors such as doxorubicin, epirubicin and mitoxanthrone (29)(30)(31). our data suggest that HDACi potentially sensitize tumor cells to treatment with capecitabine by enhancing the expression of TP.…”
Section: Discussionmentioning
confidence: 99%
“…preclinical and clinical data indicate that HDACi may interfere with the expression of pro-and anti-angiogenic genes, suggesting a synergistic effect when HDACi are combined with anti-angiogenic agents such as the anti-VEGF antibody, bevacizumab (28). In addition, HDACi have been observed to potentiate the cytotoxicity of anthracycline-type topoisomerase (topo) II inhibitors such as doxorubicin, epirubicin and mitoxanthrone (29)(30)(31). our data suggest that HDACi potentially sensitize tumor cells to treatment with capecitabine by enhancing the expression of TP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Trichostatin A has been shown to augment doxorubicin-induced apoptosis and cell death in human erythroleukemic K562 cells, anaplastic thyroid carcinoma, and A549 alveolar adenocarcinoma cells [60,61]. Similarly, SAHA and valproic acid have been shown to enhance the sensitivity of malignant cells to the effects of doxorubicin [62,63]. HDAC inhibitors induce histone hyperacetylation, resulting in a more open transcriptionally permissive chromatin conformation, a phenomenon that has been verified by MNase digestion assays [64].…”
Section: Combinatorial Therapies With Histone Deacetylase Inhibitorsmentioning
confidence: 89%
“…Although the real effectiveness of HDAC inhibitors is still a question, combination therapy with HDAC inhibitors and other agents may be an answer. In several in vitro studies, an enhanced effect was observed with combination therapy, such as depsipeptide combined with p53 gene therapy [32], doxorubicin combined with VPA [33], and HDAC inhibitors combined with proteasome inhibitor [34]. Particularly SAHA showed a synergistic effect with all of the target therapy agents in a cell study [35].…”
Section: Hdac Inhibitormentioning
confidence: 99%